2016
DOI: 10.1016/j.mce.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of granulosal bone morphogenetic protein receptor 1B density is associated with reduced ovarian reserve and the age-related decline in human fertility

Abstract: Reproductive ageing is linked to the depletion of ovarian primordial follicles, which causes an irreversible change to ovarian cellular function and the capacity to reproduce. The current study aimed to profile the expression of bone morphogenetic protein receptor, (BMPR1B) in 53 IVF patients exhibiting different degrees of primordial follicle depletion. The granulosa cell receptor density was measured in 403 follicles via flow cytometry. A decline in BMPR1B density occurred at the time of dominant follicle se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…LHR expression is suppressed by the LH surge. The LH surge downregulates GC LH receptor expression in preovulatory follicles in women [28,29]. The mid-cycle LH surge activates mural GC LH receptors which activates adenylate cyclase [30] and increases follicle cAMP levels (Fig.…”
Section: Lh Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…LHR expression is suppressed by the LH surge. The LH surge downregulates GC LH receptor expression in preovulatory follicles in women [28,29]. The mid-cycle LH surge activates mural GC LH receptors which activates adenylate cyclase [30] and increases follicle cAMP levels (Fig.…”
Section: Lh Receptormentioning
confidence: 99%
“…Higher oocyte quality was found in oocytes from follicles with high cumulus cell BMP2 expression levels [278]. Dysregulation of activin receptor-like kinase 6 (ALK6) in human GCs is correlated with decreased ovarian reserve [28]. A BMP15 single nucleotide polymorphism is associated with ovarian hyperstimulation [279].…”
Section: Bmp15mentioning
confidence: 99%
“…In comparison with the type I receptors ALK1, ALK2 and ALK7, four type I receptors ALK3, ALK4, ALK5 and ALK6 are expressed at modest levels in the human pre-antral follicles (Kristensen et al ., 2014). A recent study showed that the dysregulation of ALK6 in human GCs is associated with reduced ovarian reserve and the age-related decline in fertility (Regan et al ., 2016). …”
Section: Intra-ovarian Bmps and Oocyte–somatic Cell Interactionsmentioning
confidence: 99%
“…A total of 198 follicles were collected from 31 patients undergoing standard in vitro fertilisation treatment (Table 1). Patients were aged between 23 and 45 years, with a range of infertility factors, but limited to exclude unusual medical conditions, endocrine dysfunction, polycystic ovarian syndrome and endometriosis, and were comprised of male factor, low ovarian reserve, donor sperm or unexplained Ovulation was triggered with 10 000 IU HCG, and oocyte retrieval was 36 hours later by transvaginal oocyte aspiration (Regan et al, 2016). Body mass index (BMI) differences were not significant in this study.…”
Section: Methodsmentioning
confidence: 95%